Synergistic Effect of Microwave Calcination and Sonophotocatalytic Activity of TiO2-Montmorillonite on The Degradation of Direct Yellow 106 and Disperse Violet 1 - Issma Labib; Hocine Boutoumi; Hussein Khalaf (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The TiO2-pillared montmorillonite nanoparticles (TiO2-Mt) were prepared by the sol-gel method, then applied for the elimination of dyes in solution: CI Direct Yellow 106 (DY106) (azo dye) and CI Disperse Violet 1 (DV1) (anthraquinone dye) by the sonocatalytic, photocatalytic and sonophotocatalytic processes, in order to test the efficiency of photocatalysts, while photolysis, sonolysis, and sonophotolysis tests have been done previously. The photocatalysts (TiO2-Mt) were characterized by X-ray Diffraction (XRD), X-ray Fluorescence analysis (XRF), Brunauer-Emmet-Teller (BET), Scanning Electron Microscopy (SEM) methods, thermal and thermogravimetric analysis (TG/DTA) and the zero load point (pHpzc). Aqueous solutions of dye of an initial concentration (50 mg/L), in the presence of 1 g/L of photocatalyst, were irradiated using a mercury lamp (Hg) of 40 Mw/cm2 and put in contact with an ultrasonic probe with a frequency of 20 kHz and a power of 750 W, providing the ultrasound. The results obtained indicate that a weak, good and better dye degradation rate has been observed successively by the application of the sonocatalytic, photocatalytic and sonophotocatalytic processes, where the latter has shown a synergistic effect, while the photocatalyst TiO2-Mt/MW showed significant efficiency during the degradation, due to the beneficial effect of the microwave calcination mode. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).